Assessment of Occupational Stress among Bojnurd Bus Drivers - rajabali hokmabadi; hamid tavakoli; morteza morteza esmailzade; hossien ebrahimyan (Mazandaran University of Medical Sciences, 2018)
Introduction and purpose: Today, occupational stress is an outcome of occupational processes, factors, and conditions. The bus driver job is one of the most stressful occupations. The main objective of this study was the assessment of occupational stress level in Bojnurd city-bus drivers. Methods: This cross-sectional, descriptive-analytical study was performed on 61 bus drivers in the city of Bojnurd, Iran, who were chosen using the simple random  sampling method in 2016. The data were gathered using Philip el Rice standard job stress questionnaire. Data analysis was performed in SPSS version 18. Results: The results showed that all the drivers were male and married. The mean age of the subjects was 41±5 years, and the average working experience was 12±5 years. The average occupational stress score in drivers was 147.5±24.8. The results indicated that 97% of the drivers were under high stress. In addition, the results showed a significant relationship between job stress and work shift. However, there was not any significant association between job stress and other variables such as age, work experience, educational level, and employment type. Conclusion: High stress level in the studied drivers indicated that the implementation of a comprehensive stress management program is required.